Coral Reef Conservation Strategies for Everyone - Kathryn E. Lohr; Joshua T. Patterson (EDIS)
Corals are small animals related to jellyfish. Large groups of these animals live together and form huge interconnected colonies called reefs. Coral reefs are some of the most diverse ecosystems on the planet; an essential habitat for a wide variety of animal and plant species. About 400 million people rely on coral reef fish as a source of protein; about 6 million people make a living by catching and selling coral reef fish and invertebrates; tourism activities like SCUBA diving and snorkeling provide revenue of US $9.6 billion per year; and reefs reduce wave energy by 97%, helping to protect 197 million people in coastal areas from beach erosion, wave energy, and flooding. Learn how you can help protect these fragile, essential ecosystems from threats in this 7-page fact sheet written by Kathryn E. Lohr and Joshua T. Patterson, and published by the Program in Fisheries and Aquatic Sciences, School of Forest Resources and Conservation, September 2016.